Cost Assessment of Inpatient Care Episodes of Stroke in Romania - Lorenzovici, László; Székely, Andrea; Csanádi, Marcell; Gaál, Péter (Frontiers in Public Health, 2020)
Introduction: Stroke is the second leading cause of death worldwide and Romania is no exception. There is a high economic burden associated with the treatment of stroke patients, which puts pressure on the healthcare budget. This study aims to measure the inpatient treatment costs of stroke patients in Romania. Methods: Our retrospective analysis follows stroke patients in six Romanian hospitals at different progressivity level from different regions. Patients are identified from the official hospital databases, reported for reimbursement purposes. Mean inpatient costs incurred with the treatment of these stroke patient episodes are calculated using the gross costing method. The cost data are derived from the management control system of the study hospitals. Results: 3,155 patient episodes of stroke were identified in the study hospitals. The average cost per stroke inpatient care episode sums up to EUR 995.57 (95% CI: EUR 963.74—EUR 1 027.39) in 2017, while the overall yearly healthcare burden adds up to EUR 140 million, representing 2.18% of the total national health insurance budget and a cost of EUR 7.15 per capita. Conclusion: The hospital cost of stroke inpatient care episode in Romania is high and it represents a sizable part of the healthcare budget, but it is among the lowest in Europe, which can mainly be explained by the level of economic development of the country. As both the number of patients and the cost of acute care are expected to increase in the future, the economic burden of stroke is also expected to increase.